2008
DOI: 10.21273/hortsci.43.5.1359
|View full text |Cite
|
Sign up to set email alerts
|

Potential Sources of Resistance to Cucurbit Powdery Mildew in U.S. Plant Introductions of Bottle Gourd

Abstract: Powdery mildew (Podosphaera xanthii) can cause severe damage to cucurbit crops grown in open fields and greenhouses. In recent years, there has been an increased interest in the United States in grafting watermelon plants onto various cucurbit rootstocks. Bottle gourd plants (Lagenaria siceraria) are being used throughout the world as rootstocks for grafting watermelon. Although gourd plants are beneficial, they may still be susceptible hosts to various soilborne and foliar diseases. Bottle gourd plant introdu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 27 publications
1
33
0
Order By: Relevance
“…2004). Moreover, 18% of the isolates sampled in the Bari district remained undetermined using the set of eight differential melon genotypes, which suggests the presence of other races that may be identified using a more extensive set of differentials (Kousik et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2004). Moreover, 18% of the isolates sampled in the Bari district remained undetermined using the set of eight differential melon genotypes, which suggests the presence of other races that may be identified using a more extensive set of differentials (Kousik et al. 2008).…”
Section: Discussionmentioning
confidence: 99%
“…All six races were found in the Bari district, where cultivation of different species and cultivar of cucurbits is more extensive than in other districts, and therefore, it is likely that P. xanthii populations are under a stronger selective pressure for specific virulence factors (Krˇı´st-kova´et al 2004). Moreover, 18% of the isolates sampled in the Bari district remained undetermined using the set of eight differential melon genotypes, which suggests the presence of other races that may be identified using a more extensive set of differentials (Kousik et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Plant diseases are a major constraint in bottle gourd production (Mashilo et al ., ). Genetic sources of resistance to a number of economically important diseases have been identified in bottle gourd (Provvidenti, , ; Ling and Levi, ; Kousik et al ., ; Ling et al ., ; Sarao et al ., ), but their genetic inheritance of resistance and molecular markers useful for marker‐assisted selection remain largely unstudied. Among plant diseases, viral diseases are a major limiting factor in cucurbit crop productions.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in this study, L. siceraria PIs that belong to certain geographical regions (South Asia versus Africa or South America) showed different disease or pest resistance ( Fig. 1; group II) also have intermediate resistance to powdery mildew (Kousik et al, 2008). Edelstein et al (2000) indicated the potential of L. siceraria rootstocks in reducing infestation of the carmine spider mite on grafted watermelon scions.…”
Section: Grafting Experimentsmentioning
confidence: 55%